Evaluasi Kinerja LINAC Clinac CX Menggunakan Parameter PDD dan Profile Dose pada Lapangan Radiasi Simetri dan Asimetri di Rumah Sakit Universitas Andalas - Susi Zahara; Rico Adrial; Dian Milvita; Fiqi Diyona (Jurnal Fisika Unand, 2026)
This study aims to obtain Quality Control information on the quality of the photon beam and radiation field used for the maximum depth value (Zmak) from the results of Percentage Depth Dose measurements as well as the symmetry and flatness values ​​from the results of profile dose measurements using symmetric and asymmetric radiation fields of (10x10) cm2 and (15x15) cm2 with AAPM TG-40 standards. The results of Quality Control carried out on the LINAC show that the greater the photon beam energy and the area of ​​the field given, the greater the maximum depth value (Zmak) obtained. In the profile dose measurement, the largest symmetry value was obtained in the 1 cm offset section of 2.8% for 6 MV energy using the (10x10) cm2 field and the largest flatness value in the 3 cm off-set section of 1.9% while for 10 MV energy the largest symmetry value in the 3 cm off-set section was 4.3% and the largest flatness value in the 1 cm off-set section was 2.3%. In the field area (15x15) cm2, the largest symmetry values ​​of 6 MV and 10 MV energy were obtained at the 3 cm off-set section of 3.7% and 4.3%, and the largest flatness values ​​of 6 MV and 10 MV energy were found at the 3 cm off-set section of 2.3% and 2.1%. Therefore, the symmetry and asymmetry fields (1 cm off-set) on the LINAC are reliable enough to be used in cancer therapy treatment.